Risk Factors Associated With Residual Stones in Common Bile Duct Via T Tube Cholangiography After Common Bile Duct Exploration. Issue 26 (July 2015) - Zhang, Jian-Fei; Du, Zhao-Qing; Lu, Qiang; Liu, Xue-Min; Lv, Yi; Zhang, Xu-Feng
Abstract : Abstract: Open surgery with common bile duct (CBD) exploration and T tube drainage are still traditionally performed in a large amount of selected patients with cholelithiasis and choledocholithiasis. Confirmation of CBD clearance via T tube cholangiography after surgery is a routine procedure before T tube removal. The present study aims at investigating potential risk factors associated with residual stones in CBD via T tube cholangiography. Patients undergoing open CBD exploration and T tube drainage for choledocholithiasis in the hospital were enrolled retrospectively from January 2011 to December 2013. The clinical data were reviewed and analyzed based on computer database. Patients undergoing laparoscopic CBD exploration were excluded. Patients with CBD exploration and primary choledochotomy or choledochojejunostomy were also excluded from the study. T tube cholangiography was regularly performed 4 to 8 weeks postoperatively. Two hundred seventy-five patients undergoing open CBD exploration and T tube drainage were enrolled in the study. Thirty-five patients (12.7%) were found to have gallbladder stones but without bile duct stones intraoperatively (Group A). One hundred sixty-five (Group B) and 77 patients (Group C) were diagnosed with choledocholithiasis and hepato-choledocholithiasis in operation, respectively. Disease of hepato-choledocholithiasis, size of the previous stones, and CBD exploration without intraoperative choledochoscopy were identified as risk factors associated with residue stones via T tube cholangiography ( P < 0.001, P = 0.034, and P = 0.047, respectively). Patients with residual stones had a higher incidence of cholangitis during cholangiography than those without residual stones (8.9% vs 7.8%, P = 0.05). A scoring system based on the 3 risk factors has been set up. The incidence of residual stones were 5.6% in patients with score 0 to 1, 27.4% in patients with score 2 to 3 and 80.0% in patients with score 4 ( P < 0.001). Abdominal distension after T tube clamp might be a strong predictor of cholangiography-associated choloangitis ( P < 0.001). Intraopearative choledochoscopy should be strongly recommended as a routine procedure during CBD exploration to confirm the clearance of CBD, which could significantly lower the risk of residual stones postoperatively.